2005
DOI: 10.1002/bem.20179
|View full text |Cite
|
Sign up to set email alerts
|

DNA strand breaks are not induced in human cells exposed to 2.1425 GHz band CW and W-CDMA modulated radiofrequency fields allocated to mobile radio base stations

Abstract: We conducted a large-scale in vitro study focused on the effects of low level radiofrequency (RF) fields from mobile radio base stations employing the International Mobile Telecommunication 2000 (IMT-2000) cellular system in order to test the hypothesis that modulated RF fields may act as a DNA damaging agent. First, we evaluated the responses of human cells to microwave exposure at a specific absorption rate (SAR) of 80 mW/kg, which corresponds to the limit of the average whole body SAR for general public exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 16 publications
(12 reference statements)
5
27
0
Order By: Relevance
“…Contrarily, and in accord with our experimental data, some studies showed the electromagnetic radiations emitted by mobile phones may have little (if any) negative effect on DNA integrity (31)(32)(33)(34)(35). More specifically, Verschaeve and colleagues demonstrated that exposure for a period of 2 years, 2 h per day and 5 days per week [average wholebody specific absorption rates (SAR) of 0.3 or 0.9 W/kg], did not significantly modify DNA strand breaks in blood, liver …”
Section: Resultssupporting
confidence: 90%
“…Contrarily, and in accord with our experimental data, some studies showed the electromagnetic radiations emitted by mobile phones may have little (if any) negative effect on DNA integrity (31)(32)(33)(34)(35). More specifically, Verschaeve and colleagues demonstrated that exposure for a period of 2 years, 2 h per day and 5 days per week [average wholebody specific absorption rates (SAR) of 0.3 or 0.9 W/kg], did not significantly modify DNA strand breaks in blood, liver …”
Section: Resultssupporting
confidence: 90%
“…In contrast to our results, Koyama et al (2008) evaluated MMS effects on A172 cells and observed no decreases in viability after treatments with this compound up to 10 h, but formation of apurinic/apyrimidinic sites after 2 and 4 h; although concentration employed in their experiments was 1 mM (0.11 mg/ml), one order of magnitude below the lowest dose employed in the current study. In agreement with our findings, Sakuma et al (2006) reported a time-and dosedependent increase of DNA strand breaks (evaluated by comet assay) in A172 cells treated with MMS (2e20 mg/ml). In neurons, Luukkonen et al (2011) reported statistically significant decrease in viability and increase in primary DNA damage (comet assay) and MN frequency in SH-SY5Y cells after exposure to MMS (15e35 mg/ ml).…”
Section: Discussionsupporting
confidence: 93%
“…We previously focused on genotoxic effects of low-level RF fields from mobile radio base stations and confirmed that 2.1425 GHz RF field exposures did not induce DNA-strand breakages in human cells [Sakuma et al, 2006]. The aim of this study was to investigate whether exposure to 2.1425 GHz band CW or W-CDMA modulated signals induced a cellular stress response at the limit of the average whole-body SAR levels based on ICNIRP guidelines [ICNIRP, 1998].…”
Section: Introductionmentioning
confidence: 92%